2020
DOI: 10.1038/s41386-020-0633-z
|View full text |Cite
|
Sign up to set email alerts
|

Global connectivity and local excitability changes underlie antidepressant effects of repetitive transcranial magnetic stimulation

Abstract: Repetitive transcranial magnetic stimulation (rTMS) is a commonly-used treatment for major depressive disorder (MDD). However, our understanding of the mechanism by which TMS exerts its antidepressant effect is minimal. Furthermore, we lack brain signals that can be used to predict and track clinical outcome. Such signals would allow for treatment stratification and optimization. Here, we performed a randomized, sham-controlled clinical trial and measured electrophysiological, neuroimaging, and clinical change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 39 publications
1
63
0
Order By: Relevance
“…Neuroimaging measures can also serve as predictive biomarkers for response to rTMS. Multiple studies have linked intrinsic functional connectivity between the targeted region of PFC and ACC, anterior insula and striatum with later response to rTMS ( 74 , 125 , 200 , 245 254 ) and other antidepressant treatments ( 101 , 255 258 ). Interleaved rTMS/fMRI has shown acute effects on BOLD activation of both local and distal brain regions immediately following 1 Hz DLPFC rTMS in adults with MDD ( 89 ).…”
Section: Limitations Of the Existing Literature And Proposed Resolutionsmentioning
confidence: 99%
“…Neuroimaging measures can also serve as predictive biomarkers for response to rTMS. Multiple studies have linked intrinsic functional connectivity between the targeted region of PFC and ACC, anterior insula and striatum with later response to rTMS ( 74 , 125 , 200 , 245 254 ) and other antidepressant treatments ( 101 , 255 258 ). Interleaved rTMS/fMRI has shown acute effects on BOLD activation of both local and distal brain regions immediately following 1 Hz DLPFC rTMS in adults with MDD ( 89 ).…”
Section: Limitations Of the Existing Literature And Proposed Resolutionsmentioning
confidence: 99%
“…Consistently with these results, in an RCT on 33 unipolar depressed patients evaluating rs-fMRI connectivity changes before and after 4 weeks of rTMS, Eshel et al . (2020) observed a decreased FC in active compared to sham group between both targeted (left) DLPFC and controlateral DLPFC and between the left DLPFC and bilateral amygdala. Moreover, the authors demonstrated an increased targeted (left) DLPFC global FC in active compared to sham group.…”
Section: Resultsmentioning
confidence: 95%
“…This meta-analysis indicated that depression associated with abnormal brain network models includes various cortical and subcortical brain regions. Some clinical studies have shown that rTMS can affect the stimulated site and a transsynaptic network of interconnected areas ( Tik et al, 2017 ; Eshel et al, 2020 ). FC might be used to identify an optimal TMS target for use in MDD patients ( Wang et al, 2019 ; Cash et al, 2020 ).…”
Section: Neuroimaging-based Targeting Measurementmentioning
confidence: 99%